Nivolumab Versus Docetaxel in a Predominantly Chinese Patient Population With Previously Treated Advanced NSCLC: CheckMate 078 Randomized Phase III Clinical Trial - Wu, Yi-Long; Lu, Shun; Cheng, Ying; Zhou, Caicun; Wang, Jie; Mok, Tony; Zhang, Li; Tu, Hai-Yan; Wu, Lin; Feng, Jifeng; Zhang, Yiping; Luft, Alexander Valerievich; et al. (Journal of thoracic oncology, 2019)
Data on immuno-oncology agents in Chinese patients are limited despite a need for new therapies. We evaluated the efficacy and safety of nivolumab in a predominantly Chinese patient population with previously treated NSCLC. CheckMate 078 was a randomized, open-label, phase III clinical trial in patients from China, Russia, and Singapore with squamous or nonsquamous NSCLC that had progressed during/after platinum-based doublet chemotherapy (ClinicalTrials.gov: NCT02613507). Patients with EGFR/ALK alterations were excluded. Patients (N = 504) were randomized 2:1 to nivolumab (3 mg/kg every 2 weeks) or docetaxel (75 mg/m2 every 3 weeks), stratified by performance status, tumor histology, and tumor programmed death ligand 1 expression. The primary endpoint was overall survival (OS); secondary endpoints included objective response rate, progression-free survival, and safety. OS was significantly improved with nivolumab (n = 338) versus docetaxel (n = 166); median OS (95% confidence interval): 12.0 (10.4–14.0) versus 9.6 (7.6–11.2) months, respectively; hazard ratio (97.7% confidence interval): 0.68 (0.52–0.90); p = 0.0006. Objective response rate was 17% with nivolumab versus 4% with docetaxel; median duration of response was not reached versus 5.3 months. Minimum follow-up was 8.8 months. The frequency of grade 3 or greater treatment-related adverse events was 10% with nivolumab and 48% with docetaxel. This is the first phase III study in a predominantly Chinese population reporting results with a programmed death 1 inhibitor. In this population with previously treated advanced NSCLC, nivolumab improved OS versus docetaxel. Results were consistent with global CheckMate 017 and 057 studies.